Blunt Trauma Leading to Anterior Abdominal Wall Hernia - Khaled Abdullah Rage; Maria Ahmed; Amara Zafar; Sana Shahid; Summaya Saeed (ziauddin University, 2024)
Traumatic abdominal wall hernia (TAWH) has a reported incidence of around 1%. It is defined as herniation of intra-abdominal organs following trauma without skin penetration. High-energy trauma is often associated with intra-abdominal injury. Treatment options vary from non-operative management to surgical repair either open or laparoscopic. We present a case of a middle-aged male who presented with a history of rickshaw roll over injury. On examination, there was tender abdominal swelling with abrasions. Computerized Tomography (CT) scan confirmed the diagnosis of TAWH and free fluid in abdomen. Emergency exploratory laparotomy was performed. Mesenteric tears were repaired and primary restoration of abdominal wall was done. The patient was discharged on a fourth post-operative day without any complications. Management of TAWH should be tailored according to individual patient presentation. Midline exploratory laparotomy with the primary hernial repair is an operative intervention of choice for those with high-energy injury as there is an increased chance of accompanying visceral trauma. Keywords: Laparotomy; Trauma; Hernia.